Proceedings of the 1998 American Control Conference. ACC (IEEE Cat. No.98CH36207) 1998
DOI: 10.1109/acc.1998.703203
|View full text |Cite
|
Sign up to set email alerts
|

Model-based control of injection pultrusion process

Abstract: In this paper, we address the quality control issues in manufacturing of fiber-resin composites through a prototype process called injection pultrusion (IP). The objective is to maximize production rates while maintaining quality. It is demonstrated that a cascaded control strategy which uses an online process model is suitable in meeting this objective. The strategy uses steady-state cure and pressure models, in conjunction with an optimizer. A first principles model is exercised to generate input data for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It was shown that the model could be effectively used in die geometry design as well as optimization of the operating conditions for a given pultrudate. Voorakaranam et al (1998) presented a study on maximizing the production rates while maintaining IP quality. Based on statistical signifi cance tests, streamlined regression models were generated by identifying processing variables and parameters that have a crucial bearing on the part quality as well as by eliminating superfl uous variables.…”
Section: Experimental Studies and Optimizationmentioning
confidence: 99%
“…It was shown that the model could be effectively used in die geometry design as well as optimization of the operating conditions for a given pultrudate. Voorakaranam et al (1998) presented a study on maximizing the production rates while maintaining IP quality. Based on statistical signifi cance tests, streamlined regression models were generated by identifying processing variables and parameters that have a crucial bearing on the part quality as well as by eliminating superfl uous variables.…”
Section: Experimental Studies and Optimizationmentioning
confidence: 99%
“…At the same time, the temperature of the first zone should not exceed a certain temperature, since the power consumption might become too large due to the low infeed temperature of the fibers and resin. 21 Jaklitsch et al 22 identified an optimum die-temperature/ pull-speed combination in regard to the mechanical properties (shear-and bending strength) for an anhydride epoxy based GFRP profile. An increase in pull-speed decreased the mechanical properties slightly at the optimum dietemperature of 177°C in three zones, and a change of temperature decreased the shear strength.…”
Section: Quality Related Process Interactionsmentioning
confidence: 99%
“…At the same time, the temperature of the first zone should not exceed a certain temperature, since the power consumption might become too large due to the low infeed temperature of the fibers and resin. 21…”
Section: Introductionmentioning
confidence: 99%
“…Since the patent by Goldsworthy in 1959, 8 the continued economic importance of pultrusion over the last three decades has resulted in significant attention being paid to process modification 916 and optimisation via modelling. 9,1731…”
Section: Introductionmentioning
confidence: 99%